Breeding Climate Resilient and Future Ready Oilseed Crops - Pandey, Manish K.; Mallikarjuna, M. G.; Lohithaswa, H. C.; Aski, Muraleedhar S.; Gupta, Sanjeev (Springer, 2025)
This edited book covers the application of modern genomics tools for developing climate-smart oilseed cultivars. The book's prime focus is on utilizing available oilseed genomic resources and application of next-generation genetics and breeding tools, viz. genome-wise association mapping, genomic selection, genome editing and accelerated breeding pipelines and their efficacy for rapid development and delivery of stress-resilient oilseeds cultivars.